2017
DOI: 10.1136/bmjopen-2016-014287
|View full text |Cite
|
Sign up to set email alerts
|

Cost-related non-adherence to prescribed medicines among older adults: a cross-sectional analysis of a survey in 11 developed countries

Abstract: ObjectivesTo assess the effects of costs on access to medicines in 11 developed countries offering different levels of prescription drug coverage for their populations.DesignCross-sectional study of data from the Commonwealth Fund 2014 International Health Policy Survey of Older Adults.SettingTelephone survey conducted in 11 high-income countries: Australia, Canada, France, Germany, the Netherlands, New Zealand, Norway, Sweden, Switzerland, the UK and the USA.Participants22 532 adults aged 55 and older and liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 16 publications
7
83
0
Order By: Relevance
“…High out-of-pocket costs leave millions unable to fill prescriptions141518 and drive many into bankruptcy 1920. In the US an estimated 28 million people remain uninsured for healthcare,21 while 3.5 million in Canada lack drug coverage 14…”
Section: Access To Prescription Drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…High out-of-pocket costs leave millions unable to fill prescriptions141518 and drive many into bankruptcy 1920. In the US an estimated 28 million people remain uninsured for healthcare,21 while 3.5 million in Canada lack drug coverage 14…”
Section: Access To Prescription Drugsmentioning
confidence: 99%
“…Proportion of adults aged over 55 with cost related non-adherence to medication in 11 high income nations15…”
Section: Access To Prescription Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is burgeoning body of research on cross-sectional comparison in CRN behaviors among developed countries. For example, in a study of adults aged 55 and older and living in the community in 11 developed countries, the authors found that following the lead of the USA with 16.8% in CRN to medication, Canada had the second highest national prevalence of CRN (8.3%), followed by Australia (6.8%) [3]. While the prevalence of CRN among all older adults were much lower in France, Norway, Sweden, Switzerland and the UK, the same study showed that CRN rates vary by income, indicating a combination of effects on access to medication by income and additional insurance coverage due to low income (i.e., additional public insurance coverage associated with low income may have offset the effect of low income).…”
Section: Editorialmentioning
confidence: 99%